FISHERFOLK HUB: PUSAT KEGIATAN KOMUNITAS SEBAGAI UPAYA PEMBERDAYAAN NELAYAN DI PINGGIRAN SUNGAI MUSI , PALEMBANG - Putri Maharani, Nabilla
Rivers in the city of Palembang have become an unforgettable culture and history. The Musi River, the main river in Palembang, has a big role in local’s day to day live. Through this river, people live and carry out daily activities. However, slowly there began to be a shift in the development orientation of Palembang which was increasingly oriented towards land. Changes are not only reflected in the building, but the social order has also changed. Data shows that the number of fishermen in Indonesia is 1.27 million people by the end of 2022. This number decreased by 5.22% compared to the previous year of 1.34 million people. As for South Sumatra Province, fishermen were recorded by the end of 2022 as many as 9,142 people only. The 2022 South Sumatra Provincial Government Agency Performance Report data states that fishermen in South Sumatra are already at a prosperous level. However, this is contrary towards the admission of fishermen in the field who complain about the low daily income from fishing. The low welfare of fishermen is due to two main factors, namely lack of access (access to safe and harmless capital lending, access to education regarding sustainable fishing systems, and access to facilities and infrastructure) and a decline in the quality of commodities due to overfishing and river pollution. To answer these problems, the first thing to do is to conduct a study of previous precedents. A study written by the Organization for Economic Co-operation and Development (OECD) revealed that fisheries in coastal areas of Japan are generally operated on a small scale or even individuals and in developing fisheries in these areas, communities have a vital role. Communities are flexible, support the exchange of knowledge between fishermen, and motivate fishermen to protect the common catch area. In creating a community hub space, it is necessary to define the purpose and needs of its community. In an effort to define this space, it was found that the term fishing hub has been widely used in similar cases. When interpreted literally, a fishing hub is the centre of fishery activities. This shows that the function to be accommodated focuses on fish (commodity). Meanwhile, the expected solution to this problem focuses on fisherman (user). Therefore, a new term was coined, which is Fisherfolk Hub, a hub that focuses on users (fishers) and the creation of a strong community (folk). This project aims to empower fishermen around the Musi River by presenting a space oriented to the creation of a strong community. To achieve this vision, 3 (three) missions were composed, (1) making this project a centre of activities with high functionality, (2) presenting social spaces through circulation with many meeting points, and (3) prioritizing the characteristics of Palembang City as a waterfront city. The project is built on an area of 16,800 m2 and is located on Jalan Benteng, 9/10 Ulu, Seberang Ulu I, Palembang, South Sumatra. In the design process, there are 4 (four) main principles that want to be accommodated and answered, (1) Facilitating, (2) Growing, (3) Connecting, and (4) Uniqueness. The purpose of facilitating is to create an activity centre that provides a variety of high-quality services to accommodate various user needs. Then, growing is the presence of spaces that encourage informal knowledge exchange. Connecting is defined as an environment that increases social interaction between users, both intentionally and unintentionally. Finally, uniqueness is an effort to elevate the existence of the river as an important element in the city of Palembang and restore the image of a waterfront city. These concepts are translated in the form of architecture through a spatial program arranged in such a way. As much as 73.8% of the total building area is used for commercial purposes such as fish markets, fish auction places, and food courts. Then, 14.9% of the total building area has social and educational functions such as workshop spaces and communal areas. In the outdoor space there is a plaza and green area along with a small pier. This project is also equipped with various other supporting facilities.